Electrophysiological effects of slim straight intracochlear electrode position. Issue 12 (9th December 2020) - Ordonez, F; Sudhoff, H; Todt, I
Abstract: Objective: The electrical current distribution of a cochlear implant electrode within the cochlea is essential for post-operative hearing performance. The slim straight electrode is designed to enable the placement of contacts in a lateral or medial direction to the modiolus. The electrophysiological effect of this different contact direction is so far unknown. The aim of this study was to determine the influence of intracochlear laterally or medially directed electrode contacts on electrophysiological behaviour. Method: A slim straight electrode was inserted into the cochleae of five patients, and the neural response threshold was measured in a laterally and medially directed contact position. The cochleae in five temporal bone specimens were de-capped allowing an insertional observation of the contact position (lateral versus medial) of the electrode. Results: There was no difference in neural response threshold between a lateral and a medial position of the contacts. Temporal bone study indicated no intracochlear torsion of the electrode. Conclusion: Our study provides evidence that the intracochlear position of slim straight electrode contacts does not affect the neural response threshold.